2019
DOI: 10.1017/qua.2018.127
|View full text |Cite
|
Sign up to set email alerts
|

Hunter-gatherers subsistence and impact on fauna in the Islands of Four Mountains, Eastern Aleutians, Alaska, over 3000 yr

Abstract: This first zooarchaeological analysis for the Islands of Four Mountains (IFM), Aleutian Islands, Alaska, provides data about local hunter-gatherer resource exploitation over three thousand yr. The majority of zooarchaeological material represents faunal resources that were harvested within several kilometers of villages. Our analysis shows that IFM subsistence system was shaped by the small size of these islands, which is mostly true for all of the Aleutian Islands. The archaeological middens indicate that Ale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 10 publications
(33 citation statements)
references
References 43 publications
0
33
0
Order By: Relevance
“…5) because of severe human predation. In unit 5 at the Ulyagan archaeological site on Carisle Island, Krylovich et al (2018) identified an abundance of storm petrel remains in midden deposits that formed 500–300 cal yr BP. Ulyagan unit 2, dating to ca.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5) because of severe human predation. In unit 5 at the Ulyagan archaeological site on Carisle Island, Krylovich et al (2018) identified an abundance of storm petrel remains in midden deposits that formed 500–300 cal yr BP. Ulyagan unit 2, dating to ca.…”
Section: Discussionmentioning
confidence: 99%
“…Ulyagan unit 2, dating to ca. 150 cal yr BP, reflects sparse amounts of storm petrel remains (Krylovich et al, 2018). This combined evidence suggests that a large nesting seabird colony, which had once deposited large amounts of guano onto the landscape and ultimately into the peat deposit, was significantly reduced in size.…”
Section: Discussionmentioning
confidence: 99%
“…The information that has been obtained does serve as a baseline for understanding the fauna that would have been available to prehistoric Aleutian hunter-gatherers who occupied this island group from ca. 4000 years ago to Russian contact (Hatfield et al, 2016; Krylovich et al, forthcoming).…”
Section: Introductionmentioning
confidence: 99%
“…Examples of hunting pressure include Steller’s sea cow ( Hydrodamalis gigas ), which became extinct in the Aleutians by 1768 (Domning et al, 2007), and sea otters ( Enhydra lutris ), which were hunted to near extinction by 1911, when commercial hunting ceased (Doroff et al, 2003). Aleutian maritime hunter-gatherers used the most available offshore and inshore resources, including birds and mammals (Krylovich et al, forthcoming), for food as well as for skin, feathers, and bones to provide raw material for clothing and tools and for religious purposes (Corbett, 2016). While the prehistoric record indicates most faunal populations remained stable throughout the history of occupation in the Islands of Four Mountains, there is evidence of overexploitation of storm-petrels ( Oceanodroma spp.)…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation